Effect of Black Tea Extract and Thearubigins on Osteoporosis in Rats and Osteoclast Formation in vitro - Liang, Qingqing; Lv, Ming; Zhang, Xiaojuan; Hu, Jun; Wu, Ying; Huang, Yewei; Wang, Xuanjun; Sheng, Jun (Frontiers in Physiology, 2018)
Background: Osteoporosis is a major health problem that is closely related to substantial morbidity, mortality and decline in life quality for the aging population. Although previous studies and epidemiological evidence have demonstrated an association between black tea consumption and the prevention of bone loss, the underlying mechanism remains unclear. So, the effect of black tea extract (BTE) and thearubigins (TRs) on osteoporosis in rats and osteoclast formation in vitro were investigated. Methods: In vivo, ovariectomized (OVX) rats were used to establish osteoporosis models. To validate the model and study the effects of BTE and TRs on osteoporosis, the female Wistar rats were divided into a sham-operated group and five OVX groups including model, XLGB (as a positive control), BTE, TRs low-dose and TRs high-dose group. The rats in the four treatment groups were given the corresponding test sample for 12 weeks. Then, the body weight, femur indices, and serum biomarkers were examined and analyzed. In vitro, RAW264.7 murine macrophages were used as model of osteoclast formation. The effects of BTE and TRs on osteoclasts formation and the specific genes and protein levels of osteoclasts were determined. Results: Although there was no significant effect on the OVX-induced body weight gain by BTE or TRs, the levels of maximum bending force, cortical bone thickness and biomarker of bone resorption (acid phosphatase) can be significantly ameliorated by BTE or TRs in OVX rats. Furthermore, both of BTE and TRs can inhibit the osteoclastogenesis and diminish the expression levels of the related genes and proteins.